METODE SUGESTI-IMAJINASI DALAM PEMBELAJARAN MENULIS DENGAN MEDIA LAGU - NURSYAIDAH NURSYAIDAH (FORUM PAEDAGOGIK, 2019)
Imagination-suggestion method is a technique in writing lesson by using a song. Basically, this method is used by giving suggestions to stimulate the student’s imagination. The learning activities are divided into three stages:(l) planning, (2) activities, and (3) evaluating. The three stages in the activities are done by teacher and students before, during, and after leaning process. The application of this method inteachine descrintive writing can immnve the or remembering and organizing the facts, and giving the responds in theverbal symboland (4) the ability to make sentence variations.